A model for pricing emergent technology based on perceived business impact value. (1st January 2011) - Kar, Arpan Kumar; Pani, Ashis Kumar
Pricing is a major challenge in the marketing of emergent industrial technologies. Because of this challenge, a good strategy would be to price them based on the perceived value they would have to the client firm. Now often, such technologies have multiple attributes or features, the relative importance and the benefits of which would be different for each client. So the total perceived value from such technology would vary from client to client. This paper proposes a novel way to capture the perceived value an emergent technology may provide to the client by treating the problem as a multi-criteria decision making one. A multi-response fuzzy analytic hierarchy process is adapted for capturing the trade-offs amongst the multiple value drivers, to estimate the perceived value of the emergent technology with multiple attributes or features. The proposed methodology attempts to address a few limitations of regression-based techniques developed for the same purpose. The estimated perceived value is used to devise a pricing strategy. Finally, a hypothetical case has been used to demonstrate the proposed technique.